How Robust are Journal Rankings Based on the Impact Factor? Evidence from the Economic Sciences - Christian Seiler; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2014)
It is well-known that the distribution of citations to articles in a journal is skewed. We ask whether journal rankings based on the impact factor are robust with respect to this fact. We exclude the most cited paper, the top 5 and 10 cited papers for 100 economics journals and recalculate the impact factor. Afterwards we compare the resulting rankings with the original ones from 2012. Our results show that the rankings are relatively robust. This holds both for the 2-year and the 5-year impact factor.
Keywords: A12; A14; 330; impact factor; ranking; skewness; economics journals